Public administration : the business of government - Leveriza, Jose P. (Mandaluyong City, Philippines : National Book Store, 1990)
The business of governmentr is standard textbook for the introductory course in public administration. It is designed to help Filipinos get easily oriented on publid administration by providing them basic information for their ready reference.
Part I. The nature and scope of public administration 1 -- 1. The meaning of public administration 3 -- 2. The role of public administration in modern society 14 -- 3. The nature of bureaucracy 26 -- 4. Government and politics in public administration 40 -- 5. The ecology of public administration 50 -- Part II. Administrative organization 64 -- 6. Nature and development of organizations 66 -- 7. The types of organization 75 -- 8. The contradiction in organizations 98 -- Part III. Formal aspects of administration 115 -- 9. The management process 117 -- 10. Budgetary system 150 -- 11. Planning-programming-budgeting system 174 -- 12. Personnel administration 193 -- 13. Public relations 206 -- Part IV. Organizational behavior and development 223 -- 14. Decision-making 225 -- 15. Motivation 236 -- 16. Communication 251 -- 17. Leadership 262 -- 18. Program evaluation 275 -- Organizational development 297 -- 10. Values and ethics of public responsibility 311
Includes bibliographical references and index.
Keywords: PUBLIC ADMINISTRATION